2021
DOI: 10.3390/educsci11050193
|View full text |Cite
|
Sign up to set email alerts
|

School Effectiveness in Multilingual Education: A Review of Success Factors

Abstract: School effectiveness research (SER) and bi/multilingual education research have been largely developed as separate research paradigms. Hence, SER research does not facilitate clear conclusions on bi/multilingual (the term ‘multilingual’ is used henceforth) education and its effectiveness. Despite the intensification of multilingual education research over the last four decades, only a few authors and studies have focused on offering a compact overview of what factors need to be in place for the programs to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Language proficiency plays a crucial role in educational attainment and intergenerational mobility. Multilingualism has been associated with improved cognitive skills, academic performance, and access to higher education among immigrant populations (Kirss et al, 2021;Odulaja et al, 2023). Additionally, maintaining proficiency in one's native language alongside acquiring proficiency in the host country's language can help preserve cultural identity and facilitate intergenerational transmission of cultural capital.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Language proficiency plays a crucial role in educational attainment and intergenerational mobility. Multilingualism has been associated with improved cognitive skills, academic performance, and access to higher education among immigrant populations (Kirss et al, 2021;Odulaja et al, 2023). Additionally, maintaining proficiency in one's native language alongside acquiring proficiency in the host country's language can help preserve cultural identity and facilitate intergenerational transmission of cultural capital.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this study, we define multilingualism at the individual level as a person's ability to use two or more languages and "easily switch from one language to another" [31] (p. 158). From the point of view of multilingualism, languages are considered as separate language systems, and not dialects, styles or registers within one language system [32]. Teachers may not always be multilingual, as some native speaker teachers speak only one language, especially those who teach English [33].…”
Section: Multilingualismmentioning
confidence: 99%
“…Despite such high context specificity and the different languages involved in the vast body of research on bilingual education, a myriad of studies has reported the innumerable advantages of this educational phenomenon, being evident mainly at language, cognitive, attitude, and content learning levels [26][27][28][29]. Such advantages have given rise to innumerable research studies in different contexts and from different pedagogical approaches.…”
Section: Bilingual Education: Concept and Typesmentioning
confidence: 99%